A nonalcoholic fatty liver disease model in human induced pluripotent stem cell-derived hepatocytes, created by endoplasmic reticulum stress-induced steatosis - Maddalena Parafati; R. Jason Kirby; Sepideh Khorasanizadeh; Fraydoon Rastinejad; Siobhan Malany (The Company of Biologists, 2018)
Hepatic steatosis, a reversible state of metabolic dysregulation, can promote the onset of nonalcoholic steatohepatitis (NASH), and its transition is thought to be critical in disease evolution. The association between endoplasmic reticulum (ER) stress response and hepatocyte metabolism disorders prompted us to characterize ER stress-induced hepatic metabolic dysfunction in human induced pluripotent stem cell-derived hepatocytes (hiPSC-Hep), to explore regulatory pathways and validate a phenotypic in vitro model for progression of liver steatosis. We treated hiPSC-Hep with a ratio of unsaturated and saturated fatty acids in the presence of an inducer of ER stress to synergistically promote triglyceride accumulation and dysregulate lipid metabolism. We monitored lipid accumulation by high-content imaging and measured gene regulation by RNA sequencing and reverse transcription quantitative PCR analyses. Our results show that ER stress potentiated intracellular lipid accumulation by 5-fold in hiPSC-Hep in the absence of apoptosis. Transcriptome pathway analysis identified ER stress pathways as the most significantly dysregulated of all pathways affected. Obeticholic acid dose dependently inhibited lipid accumulation and modulated gene expression downstream of the farnesoid X receptor. We were able to identify modulation of hepatic markers and gene pathways known to be involved in steatosis and nonalcoholic fatty liver disease (NAFLD), in support of a hiPSC-Hep disease model that is relevant to clinical data for human NASH. Our results show that the model can serve as a translational discovery platform for the understanding of molecular pathways involved in NAFLD, and can facilitate the identification of novel therapeutic molecules based on high-throughput screening strategies.